Kontribusi Kepemimpinan Spiritual Terhadap Komitmen Afektif Melalui Spiritualitas Di Tempat Kerja Pada Karyawan Bank Syariah Di Kota Yogyakarta - Siti Rahayu; Erika S Kusumaputri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2016)
This study was aimed to determine the contribution of spiritual leadership toward affective commitment through the mediating of spirituality at work. Participants were 73 (N=73) employee of Syariah Bank in Yogyakarta. Cluster random sampling is used as the sampling technique. Instrument of data collection in this study is using a scale of spiritual leadership, a scale of affective commitment and a scale of spirituality at work. The method of data analysis using a path analysis developed from regression analysis. The result of path analysis indicate that the indirect effect was significant (p2 0.226 x p3 0.772 = 0.175) with significance level p=0.000 (p<0.05), and direct effect of 0.553 with significance level p=0.000 (p<0.05). Therefore total effect is direct effect that is added to indirect effect of 0.175 + 0.553 = 0.728 (72.8%) with significance level p=0.000 (p<0.05). This means that hypotheses was accepted, there is influence spiritual leadership toward affective commitment through spirituality at work on employee syariah bank, in which the higher spiritual leadership exist, than will improve affective commitment through spirituality at work that also higher. Furthermore there are 27.2% of the affective commitment are affected by another variable besides spiritual leadership and spirituality at work.Â Keywords: Affective Commitment, Spiritual Leadership, Spirituality at work, Path Analysis.